Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Problem Based Learning (PBL) Pada Materi Ekosistem Kelas V Di SDN 3 Mataram - Rahman, Arif; Zain, Moh. Irawan; Musahadah, Musahadah (Journal of Science Instruction and Technology, 2023)
This study aims to determine the increase in science learning outcomes through the problem based learning (PBL) model on environmental change material for class V at SDN 3 Mataram. This research is a classroom action research. This research was carried out in 2 cycles. Each cycle consisted of 4 stages, namely planning, implementation of observation and reflection. The data collection techniques used were tests, observation and documentation while the data analysis technique used was a qualitative analysis model. Based on the research results, it can be concluded that there is an increase in science learning outcomes after holding class action using the problem based learning (PBL) learning model. class 54.5% (low learning achievement category) cycle I to 74.7% (enough learning achievement category) and cycle II obtained an average class of 80.1% (high learning achievement category). Thus a recommendation can be put forward that the application of the problem based learning (PBL) learning model can improve science learning outcomes for fifth grade students at SDN 3 Mataram.